Estimation of micronutrients and heavy metals of monoculture, polyculture and termitoria soils (in pollachi and udumalpet taluks) - KALAICHELVI. S; EZHILI. N (International Journal of Pharma and Bio Sciences, 2018)
The aim of this research is to calculate the variation in micronutrients Manganese (Mn), Zinc (Zn), heavy metals Copper (Cu) and Iron (Fe) of monoculture and polyculture soils compared with the termitoria soil from Pollachi and Udumalpet in Coimbatore and Tirupur Districts, Tamil Nadu, India from March 2013 to February 2014. The level of Manganese and Zinc were determined based on the reaction of ions with an acidified molybdate reagent to yield a phophomolybdate complex. The concentrations of Cobalt and Iron were determined using Flame photometer, based on the method described in APHA. When compared to monoculture and polyculture soils, the termitoria soil increased the level of micronutrients was found, favours agriculture and retains the plant nutrients in the soil. In the same way the heavy metal concentration (Copper and Iron) level was also estimated. The result of heavy metals showed positive correlation with agriculture. Polyculture soil contains more nutrients when compared with monoculture soil. The study showed highly positive correlation between termitoria soil, monoculture and polyculture soils. The result highlights the value of termites and their beneficial role on soil and agriculture. The termitorium present in the monoculture and Polyculture land indirectly helps the agricultural soil to get improved with increased level of micronutrients and heavy metals through the chance of mixing mound soil by the wind, rain ect. It is right time for us to brand the terminology “termites are farmer’s friend”.